THE RELATIONSHIP BETWEEN EMPLOYEE ENGAGEMENT AND BONUS COMPENSATION TO MARKETING STRATEGY IMPROVEMENTIN INDONESIAN SMES - Burhanuddin Burhanuddin (INTERNATIONAL JOURNAL OF FINANCIAL ECONOMICS, 2025)
This study examines the complex connections among employee involvement, bonus pay, and enhancement of marketing strategies in Small and Medium-sized Enterprises (SMEs) in Indonesia. A thorough study was carried out, collecting feedback from 268 individuals from various sectors and job positions. The research uses Structural Equation Modeling with Partial Least Squares (SEM-PLS) to examine the data. The results show important connections: employee involvement has a good effect on upgrading marketing strategies, and more pay is crucial in boosting employee engagement and directly affecting the effectiveness of marketing strategies. The research provides useful information for Indonesian small and medium-sized enterprises looking to enhance employee interactions and reward systems to achieve better marketing results.